With the Help of MOM: Mitochondrial Contributions to Cellular Quality Control. Issue 6 (June 2017) - Braun, Ralf J.; Westermann, Benedikt
Abstract : Mitochondria are essential organelles because they have key roles in cellular energy metabolism and many other metabolic pathways. Several quality control systems have evolved to ensure that dysfunctional mitochondria are either repaired or eliminated. The activities of these pathways are crucial for cellular health because they maintain functional mitochondria. In addition, the cytosolic ubiquitin–proteasome system (UPS) and the mitochondria-associated degradation pathway (MAD) share some of their core components, are functionally tightly interconnected, and mutually modulate their activities. Thus, the mitochondrial outer membrane (MOM) actively supports quality control systems in extramitochondrial compartments. Furthermore, mitochondrial quality surveillance systems also act on cytosolic or endoplasmic reticulum (ER) substrates and modulate immune responses. Therefore, mitochondria contribute to cellular quality control and homeostasis on several levels. Trends: The maintenance of mitochondrial health is crucial for the maintenance of cellular health. Mitochondria counteract potentially detrimental processes that emerge in the cytosol or other cellular compartments, thereby contributing to the maintenance of cellular fitness. Given that the activities of mitochondrial and cytosolic quality control systems are tightly interconnected, mitochondria are able to trigger beneficial stress responses in the cytosol. Recent evidence suggests that mitochondria actively contribute to quality control and proteostasis of extramitochondrial compartments and modulate certain immune responses. In yeast, mitochondria immobilize stress-induced protein aggregates to prevent their inheritance by the daughter cell.